Enhanced Replication of Highly Pathogenic Influenza A(H7N9) Virus in Humans - Seiya Yamayoshi; Maki Kiso; Atsuhiro Yasuhara; Mutsumi Ito; Yuelong Shu; Yoshihiro Kawaoka (Emerging Infectious Diseases, 2018)
To clarify the threat posed by emergence of highly pathogenic influenza A(H7N9) virus infection among humans, we characterized the viral polymerase complex. Polymerase basic 2–482R, polymerase basic 2–588V, and polymerase acidic–497R individually or additively enhanced virus polymerase activity, indicating that multiple replication-enhancing mutations in 1 isolate may contribute to virulence.